Cogging torque minimisation of PM synchronous motor using genetic algorithm - Cvetkovski Goga, Petkovska Lidija (IOS Press, 2014)
The minimization of the torque ripple in permanent magnet synchronous motors (PMSM) is generally achieved by a special motor design which in the design process involves a variation of many geometrical motor parameters. In this paper a new approach is introduced where genetic algorithm is used as an optimization tool where the maximum value of the cogging torque is used as an objective function. Therefore a proper mathematical presentation of the cogging torque for the analysed synchronous motor is developed. Finally the initial motor and the optimized motor model are modelled in FEMM software which is based on finite element method. The cogging torque is analytically and numerically calculated and the results for both models are presented.
Keywords: Permanent magnet synchronous motor, optimization, genetic algorithm, cogging torque, finite element method